Viticultural performance of Cabernet Sauvignon clones in highland region of southern Brazil Desempenho vitícola de clones de Cabernet Sauvignon em região de altitude do sul do Brasil - Marcon Filho J.L.* (2019)
© 2019 Revista Brasileira de Fruticultura. All rights reserved.The Cabernet Sauvignon (CS) cultivar is one of the most widely planted wine grapes in Brazil. The final grape quality depends on the clone type, rootstock, and the terroir. This study aims to assess and characterize the effects of seven combinations of CS clones grafted onto two rootstocks on the physical–chemical parameters and productivity of the grapes in the highland of southern Brazil, during the 2012-2013, 2013-2014, 2014-2015, and 2015-2016 growing seasons. The experiment was carried out in a 14-year-old commercial vineyard, located in São Joaquim municipality, Santa Catarina State, trained on a vertical shoot position system on a double cordon with spur pruning. The treatments consisted in a completely randomized experimental block of the combination (clone/rootstock) of CS 169, 337, 341, and R5 clones grafted onto the Paulsen 1103 (P1103) rootstock, and 169, 170, and 339 clones grafted onto the Courdec 3309 (C3309) rootstock. There were significant differences among the combinations of CS grapes on productivity, physical, and chemical parameters and grape maturation. The data of principal component analysis showed that 339/C3309 and 337/P1103 combinations were the most productive, whereas the R5/P1103, 170/C3309, and 169/C3309 combinations were the best for potential winemaking under the edaphoclimatic conditions of the highlands of southern Brazil in all growing seasons evaluated. Index terms: Vitis vinifera; clonal selection; rootstock; grape composition; yield components.